Absence of p300 induces cellular phenotypic changes characteristic of epithelial to mesenchyme transition. - Krubasik, D; Iyer, N; English, W; Ahmed, A; Vias, M; Roskelley, C; Brenton, J; Caldas, C; Murphy, G (2006)
p300 is a transcriptional cofactor and prototype histone acetyltransferase involved in regulating multiple cellular processes. We generated p300 deficient (p300-) cells from the colon carcinoma cell line HCT116 by gene targeting. Comparison of epithelial and mesenchymal proteins in p300- with parental HCT116 cells showed that a number of genes involved in cell and extracellular matrix interactions, typical of 'epithelial to mesenchyme transition' were differentially regulated at both the RNA and protein level. p300- cells were found to have aggressive 'cancer' phenotypes, with loss of cell-cell adhesion, defects in cell-matrix adhesion and increased migration through collagen and matrigel. Although migration was shown to be metalloproteinase mediated, these cells actually showed a downregulation or no change in the level of key metalloproteinases, indicating that changes in cellular adhesion properties can be critical for cellular mobility.